La GIZC et le patrimoine culturel en droit français - Nicolas Boillet (VertigO)
Integrated Coastal Zone Management includes consideration of social and cultural issues and also specifically concerns cultural heritage. Several texts on ICZM, such as the Madrid ICZM protocol (2009), contain provisions for taking cultural heritage – sometimes qualified as common heritage – into account. Consequently, projects claiming to use ICZM should reconsider the concept of coastal or maritime cultural heritage, although it is difficult to define such heritage using the classic conservation tools of heritage law that are not specific to the coastal situation. The ICZM process causes cultural marine heritage to be more greatly subjected to the principles of sustainable development, and actions toward the economic development of these areas, notably for tourism.